2009
DOI: 10.1371/journal.pgen.1000581
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Stress-Regulated Gene Expression in Duplicate Genes of Arabidopsis thaliana

Abstract: Due to the selection pressure imposed by highly variable environmental conditions, stress sensing and regulatory response mechanisms in plants are expected to evolve rapidly. One potential source of innovation in plant stress response mechanisms is gene duplication. In this study, we examined the evolution of stress-regulated gene expression among duplicated genes in the model plant Arabidopsis thaliana. Key to this analysis was reconstructing the putative ancestral stress regulation pattern. By comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 78 publications
10
124
0
Order By: Relevance
“…The downside is that paralog-specific expression patterns are masked, as our qPCR results of the natterin like gene family show ( Figure 3 and S1 Figure). Recent rainbow trout data shows most paralogs from the latest whole genome duplication event retain the same expression pattern 32 indicating that this scenario is probably uncommon; hence it is of considerable interest when two paralogs show distinct expression patterns 82 . In their analysis of the Arctic charr gill transcriptome, Norman et al (2014) 16 also used Illumina sequencing technology to evaluate expression.…”
Section: Discussionmentioning
confidence: 99%
“…The downside is that paralog-specific expression patterns are masked, as our qPCR results of the natterin like gene family show ( Figure 3 and S1 Figure). Recent rainbow trout data shows most paralogs from the latest whole genome duplication event retain the same expression pattern 32 indicating that this scenario is probably uncommon; hence it is of considerable interest when two paralogs show distinct expression patterns 82 . In their analysis of the Arctic charr gill transcriptome, Norman et al (2014) 16 also used Illumina sequencing technology to evaluate expression.…”
Section: Discussionmentioning
confidence: 99%
“…An evolutionary consequence for duplicated loci was referred to as subfunctionalization (Moore and Purugganan, 2005). Recently, the models involving epigenetic silencing of duplicate genes or purifying selection for gene balance have also been proposed (Zou et al 2009). …”
Section: Evolutionary Forces For Hsp17 Duplication Copiesmentioning
confidence: 99%
“…The generation of new evolutionary novelties will lead to environmental adaptations. Most studies on the evolution of gene duplications focus on examining whole-genome duplications of model organisms (Zou et al, 2009) and the macroevolutionary patterns of gene diversification (Hanada et al, 2008). In contrast, we know very little about the relative importance of the two evolutionary forces, neutral genetic drift and positive selection, which shape the ultimate functional fate of the duplicate gene pair (Moore and Purugganan, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tandem duplications seem to have a more important role in shaping genomes for stress adaptations than polyploidy, segmental transposition-duplications, or ectopic duplication and translocation [40]; recombination and tandem duplication events may both become accelerated by environmental challenges [29]. As the result of unequal crossing-over during recombination, tandem duplications vary in their 'genetic neighborhoods', with copies receiving different regulatory motifs that can lead to drastic changes in expression [40].…”
Section: Stress Adaptation By Gene Duplicationmentioning
confidence: 99%
“…As the result of unequal crossing-over during recombination, tandem duplications vary in their 'genetic neighborhoods', with copies receiving different regulatory motifs that can lead to drastic changes in expression [40]. A comparative study on plant genomes ranging from Arabidopsis to Physcomitrella showed genes associated with defense, transport functions, or abiotic stress responses enriched in tandem duplicates, whereas duplicates due to other mechanisms included genes enriched in other intracellular regulatory roles [41].…”
Section: Stress Adaptation By Gene Duplicationmentioning
confidence: 99%